Caracterização termo-óptica quantitativa de fibras de poliéster e seus compósitos com polietileno - Bicalho, Luciana Assumpção (2015)
The work herein aims at investigating the thermo-optical behavior of polyethylene terephthalate and its composites with polyethylene, in real time, by means of an optical module recently developed in our research group. Polyethylene terephthalate was the material of choice because of its various thermal transitions and optical properties. Multilayered films comprising fibers of polyethylene terephthalate sandwiched with polyethylene films were prepared to study the influence of a matrix on the fibers thermo-optical responses. This was investigated by coupling a hot-stage onto a stand-up optical microscopy and placing the optical module into the analyzer slot. The module encompasses adjacent photocells with/without analyzer to read both turbidity (resulting from scattered light) and depolarized light intensity due to crystallites. In order to handling the signal a software was developed in LabView 8.6 platform from National Instruments for data collection, real-time calculation, screen presentation and data saving. In addition, all parameters set on the CSS 450 can be controlled via software. Finally, a digital camera was coupled on the top of the microscope (ocular tube) to allow for both image capturing and video recording. The structural changes arising from the thermal protocol were assessed following the elicited responses present at the depolarized light intensity and turbidity. Both optical phenomena were sensitive to polymer thermal transitions such as glass transition and melting temperature. The photocell with analyzer is able to collect the thermal transitions and the cold crystallization typical of polyethylene terephthalate resin. The introduction of the optical path difference, an alternative way of displaying the optical data as function temperature, makes easier the understanding of molecule mobility, cold crystallization and melting. The narrow relation existent between the optical behavior and that obtained from the differential scanning calorimetry measurements leaded to the validation of the thermo-optical method, which has the advantage to provide additional information on the fiber orientation and stretching.